Políticas del gobierno mexicano en la región fronteriza norte - Herrera Ramos, J. Mario (El Colegio de México A.C., 1988)
In this article an appraisal is made of the programs and policies introduced by the Mexican government since 1848 concerning its northern border zone. The principal objective of such programs and policies is to ensure the economic, political, and social integration of the northern border zone vis-a-vis the rest of the country. This study purports to effect a critical evaluation of the results obtained with regard to the objective of integration. The conclusion is reached that this goal has not been achieved and that it is necessary to question, and perhaps even challenge, the validness of integration as a fundamental element of regional and urban policies on Mexico's northern border zone.